2012
DOI: 10.1007/s10750-012-1021-4
|View full text |Cite
|
Sign up to set email alerts
|

Sediment resuspension: rescue or downfall of a thermally stratified eutrophic lake?

Abstract: The aim of this study was to estimate the effect of sediment resuspension, a common phenomenon in many lakes, on the phosphorus budget of a eutrophicated lake. We used two different approaches, mass balance calculations and spatially comprehensive resuspension measurements, to determine the level of phosphorus loading from which rehabilitation action is started in a dimictic north temperate lake. The effect of resuspension was assumed to be significant, since it often is a governing process for cycling of mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Wind has been demonstrated to impact sediment-water interactions, particularly in large shallow lakes (Bachmann et al, 2000;Havens et al, 2007;Kelderman et al, 2012;Spears et al, 2012). Wind-induced resuspension mixes P-rich sediment particles and interstitial P into the water column, and this transport at any given time can be orders of magnitude greater than other inputs of P such as by diffusion and external loading (Havens et al, 2007;Niemistö et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Wind has been demonstrated to impact sediment-water interactions, particularly in large shallow lakes (Bachmann et al, 2000;Havens et al, 2007;Kelderman et al, 2012;Spears et al, 2012). Wind-induced resuspension mixes P-rich sediment particles and interstitial P into the water column, and this transport at any given time can be orders of magnitude greater than other inputs of P such as by diffusion and external loading (Havens et al, 2007;Niemistö et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Destratification, physical removal or harvesting and sediment dredging are also possible control methods although they contain the significant drawback that they are very expensive [71]. Destratification could be done by pumping nutrient and oxygen rich waters from the surface down to the hypolimnion using an axial flow propeller pump [103] [108].…”
Section: Physical and Chemical Methodsmentioning
confidence: 99%
“…It is unlikely that porewater would be a major source of P given the low SRP concentrations in the Bear Lake porewater (usually < 20 µg/L; data not shown). However, phosphate ions desorbing from sediment, once in suspension, could possibly be a significant source of P (Søndergaard et al 2003, Istvánovics et al 2004, Steinman et al 2006, although prior studies also have shown that the effect of sediment resuspension is extremely variable in space and time (Cyr et al 2009, Niemistö et al 2012). …”
Section: Anoxicmentioning
confidence: 99%